Expansion of attentional scope modulates postural control, motor strategies, and attentional network connectivity in healthy adults: a proof-of-concept mixed-methods study - Goto, Keisuke; Watanabe, Rui; Yamamoto, Satoshi; Lim, Vivian Sihan; Shimada, Ryusuke; Kuruma, Hironobu; Senoo, Atsushi; Ikeda, Yumi (Frontiers Media S.A., 2026)
Introduction:
Plantar sensory input plays a key role in postural control. However, training protocols that solely amplify this bottom-up input have demonstrated inconsistent efficacy. We hypothesized that a top-down protocol using plantar sensations as a perceptual anchor and expanding the attentional scope from localized plantar sensations to a whole-body reference frame would yield greater improvements than sensory discrimination alone.
Methods:
Forty-eight healthy adults (N = 48) participated in a single 10-minute session of either Sensory Discrimination Only (SDO) or Sensory Discrimination with Expansion of Attentional Scope (SDE). The SDE protocol employs a brief therapeutic dialogue to facilitate this expansion. The Index of Postural Stability (IPS) was assessed at baseline (T0), immediately after the training (T1), and 30 min after (T2). Semi-structured interviews at T0/T1 were text-mined to quantify motor strategies. Resting-state functional magnetic resonance imaging (rs-fMRI) data were collected at T0/T1 for region-of-interest (ROI)-to-ROI connectivity analyses, focusing on major large-scale brain networks.
Results:
The SDE group demonstrated a significant IPS improvement (ΔIPS ≈ + 0.09, dz = 0.42) and maintained this improvement at 30 min (T0 vs. T2: dz = 0.32), whereas the SDO group demonstrated no change. Qualitative analyses of self-reported motor strategies in the SDE group indicated attentional expansion beyond a plantar perceptual anchor toward whole-body alignment, reflected by increased references to the shoulders while foot-related references remained common. In rs-fMRI, a cluster within attentional circuitry, including the salience and ventral attention networks, demonstrated a significant group × time interaction [threshold-free cluster enhancement [TFCE]/family-wise error [FWE]-corrected p < .05], characterized by reduced connectivity following SDE and a trend toward increased connectivity following SDO.
Conclusions:
In this proof-of-concept study, expanding attentional scope from a plantar perceptual anchor toward a whole-body reference frame was associated with immediate, group-level changes across measures. Postural stability improved, alongside changes in self-reported motor strategies and resting-state connectivity within attentional circuitry. Enhancing sensitivity to bottom-up plantar input remains fundamental; however, these findings suggest a potential next step—learning how to interpret and use plantar input as a whole-body reference signal for balance regulation. Confirmation in randomized and longitudinal studies, including evaluation in clinical populations, is warranted.